Link and Match Socialization of Maritime Vocational College Graduates in the Field of Shipping with the Business and the Industrial World - Astriawati, Ningrum; Dekanawati, Vivid; Sahudiyono, Sahudiyono; Kusuma, Ade Chandra; Subekti, Joko; Handojo, Budi (IJCS: International Journal of Community Service, 2024)
The "link and match" program intensified by the Ministry of Education and Culture does not only benefit the world of education which makes it easier to adjust to the industry. The purpose of this community service is to provide socialization about Link and Match Maritime Vocational College Graduates in the Field of Shipping with the Business World and the Industrial World and know about the absorption of graduates produced by universities with the Business World and the Industrial World. The method used in this community service activity is socialization about Link and Match Maritime Vocational College Graduates in the Field of Shipping with the Business World and the Industrial World. The results of dedication in the form of socialization about Link and Match Maritime Vocational College Graduates in the Field of Shipping with the Business World and the Industrial World ran smoothly. In addition, the average percentage of absorption of vocational school graduates at Yogyakarta Maritime College was obtained through the Link and Match Program which was created to synergize vocational education with the industrial world to increase the absorption of vocational school graduates so that they can become reliable workers while saving expenses to become new human resources following industry needs of 92.11%. The absorption of graduates for graduates of the D3 Marine Transportation Management study program is 84.00%, the absorption of graduates for the D3 Ship Machinery study program is 100% and the absorption of graduates for the D3 Nautical Studies study program is 100% of the total 70.37% of tracked graduates.